Efek Penyuluhan Gizi Dengan Media Leaflet Terhadap Tingkat Pengetahuan Tentang Anemia Pada Remaja Putri Di Smp Kristen 1 Surakarta - ROKHMAWATI, Indah Asyri, Tuti Rahmawati, S.Gz.,M.Si, Elida Soviana, S.Gz., M.Gizi (2015)
Background : Anemia is one of the major nutritional problem that affects almost half of young women in Indonesia. Nutritional counseling in adolescent girls is given with the aim to address the problem of anemia. Nutritional counseling is an effort to increase knowledge of young women about anemia. Leaflet as nutritional counseling media facilitate the delivery of information and receiving messages for young women. Objective : This research aims to know determine the effects of nutrition counseling with leaflets media to increase knowledge about anemia in adolescent girls in SMP Kristen 1 Surakarta. Research Methods : Type of this research was quantitative with quasi experiment one group pre and post test design. The subject of this research were eighth grader who attend SMP Kristen 1 Surakarta by 96 female students with a total sample of 48 subjects. Data collection research using primary data questionnaire. Analytical techniques used is the Wilcoxon rank test . Results of the Research : Wilcoxon Rank Test results obtained the value of significance of , (p-value) 0.000, then therefore there is a significant difference in the level of knowledge about anemia in adolescent before and after nutritional counseling with leaflets in SMP Kristen 1 Surakarta. Conclusion : There was the difference in the level of knowledge about anemia in adolescents before and after nutritional counseling with media leaflets in SMP Kristen 1 Surakarta.